Before the verdict: the hidden cost of stigmatising the accused - Roslan, Muhammad Azril (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
In modern legal systems, including Malaysia’s, the presumption of innocence is fundamental, yet public opinion often ignores this principle by judging accused individuals as guilty the moment they are arrested. The legal term Orang Kena Tuduh (OKT) simply identifies someone facing charges, not someone proven guilty. While police are responsible for investigating and collecting evidence, only the courts have the authority to determine guilt, reflecting the crucial separation of powers that protects fairness and justice.